Seismic Response of G+8 RC Building Frame having Setback Irregularity and Subjected to Mainshock-Aftershocks Sequences - Tulsi Meena; M.S. Hora (Engineering Research: Perspectives on Recent Advances Vol. 6, 2025)
The earthquake sequences are characterized by mainshocks followed by aftershocks, which pose significant challenges to the irregular building structures having setback irregularities. These irregular buildings already have complex structural behaviour and face heightened vulnerability when subjected to such sequential seismic events. The initial mainshock substantially weakens the structure’s residual capacity, leaving it more susceptible to damage from subsequent aftershocks. This interplay between setback irregularity and earthquake sequences presents a critical area of concern in structural engineering and seismic risk assessment. The present study investigates the seismic response of an irregular G+8 RC building subjected to mainshock-aftershock sequences. For this purpose, three building models are examined namely; a regular building (B1), a building with one-third of its floors having setback irregularity (B2), and a building with two-thirds of its floors having setback irregularity (B3). Each model is subjected to three different types of ground motion scenarios including single mainshocks and mainshock-aftershock sequences and analysed using the linear time history method and the latest version of ETABS V22.3.0. The research findings highlight the significant impact of aftershocks on the seismic performance. The base shear decreases under main shock-after shock (MSAS) compared to Main shock (MS), indicating reduced lateral force resistance, with B1 showing the highest base shear (25013.17 kN) and B3 the lowest (5495 kN) due to setback irregularities. It is concluded that the irregular building model B3 exhibits the highest maximum displacement of nearly 214 mm and the highest increase of nearly 18% in inter-storey drift (MS to MSAS events) due to the lateral seismic forces caused by the Coalinga earthquake. It means that the setback irregularities amplify lateral deformations, thus making such structures more vulnerable to strong seismic excitations. On the contrary, the same model exhibited the lowest base shear under the MSAS event during the Valparaíso earthquake which indicates its instability to resist excessive deformation under lateral forces and has a tendency to collapse. The results from investigations provide valuable insights into the design and assessment of irregular RC structures in seismically active regions, thus contributing to the development of more resilient building practices.